Adaptation of the 20-Item Prosopagnosia Index for the Screening of Developmental Prosopagnosia in Mexico - Mejía Ramírez, Manuel Alejandro; Cardoso, Agustin; Lozoya, Vania; Bobes, Antonieta (My University, 2026)
Developmental prosopagnosia (DP) is a lifelong condition characterized by difficulties in recognizing faces despite intact vision and intelligence. The 20-Item Prosopagnosia Index (PI20) is a widely used self-report instrument for screening face recognition deficits. However, no standardized Spanish version of the PI20 existed prior to this study, limiting its applicability in Mexican populations and other Spanish-speaking contexts where no validated version exists. This study aims to adapt and validate the PI20 for use in Mexican Spanish, supporting its linguistic and contextual appropriateness for use in the Mexican population. Study 1 involved a rigorous translation and cultural adaptation process, including forward translation by multiple independent translators, expert panel review, and cognitive interviews with bilingual Mexican participants. Qualitative analysis of these interviews identified semantic and conceptual issues in several items, which were subsequently revised. A pilot test with 15 participants confirmed the clarity and feasibility of the adapted version, supporting its content validity. Study 2 evaluated the psychometric properties of the adapted PI20 in a sample of 333 adults. The results showed high internal consistency (McDonald’s omega and Cronbach’s alpha = .84) and good test–retest reliability (ICC2,1= .81). Confirmatory factor analysis supported a unidimensional structure consistent with the original scale, while exploratory analysis revealed two correlated components that did not undermine the overall model. The adapted PI20 showed a moderate negative correlation with the Cambridge Face Memory Test (r(316) = -.229, p < .001), supporting convergent validity, and no significant association with the Cambridge Car Memory Test (r(313) = -.106, p = .061), supporting discriminant validity. These findings suggest that the Mexican Spanish version of the PI20 is a reliable and valid instrument for assessing self-reported facial recognition difficulties in Spanish-speaking Mexican adults. This adaptation represents an important step toward the availability of linguistically and contextually appropriate tools for research and screening purposes.
Collabra: Psychology
Keywords: Prosopagnosia; item; Screening; Campus Tijuana